Depiction of Patriarchal Society in Disney's Cinderella - Hani , Umi; Subhan, Yan Ardian; Rasyad, Himsyar (Jurnal Humaniora dan Ilmu Pendidikan, 2024)
Purpose: The objective of this study is to examine the patriarchal society of Disney’s Cinderella using patriarchal analysis. Cinderella is a well know adaptation of the fairytale. Although seemingly a harmless cartoon about princess, it actually has a harmful representation of a patriarchal society. Methodology/approach: Descriptive qualitative and library research methods were used to analyze and describe the quotations and transcripts based on the Kate Millet theory of sexual politics.  Results/findings: From the research, two signs of patriarchal society are depicted: (1) the ideological sign where every male character in the movie thinks of women as something to be subjugated at and to be married to continue the family line. (2) Psychological signs where the female character including Cinderella is accepting their traditional role as home maker and not making any effort to escape the patriarchy Limitations: This study depicted many signs of patriarchal society in the film, but this discussion is limited only into two clear signs of patriarchal society Contribution: Hopefully, this analysis can contribute to the field of film, literary studies, and sociological perspectives.